2021
DOI: 10.3390/jpm11090937
|View full text |Cite
|
Sign up to set email alerts
|

Access to Prenatal Testing and Ethically Informed Counselling in Germany, Poland and Russia

Abstract: The development of new methods in the field of prenatal testing leads to an expansion of information that needs to be provided to expectant mothers. The aim of this research is to explore opinions and attitudes of gynecologists in Germany, Poland and Russia towards access to prenatal testing and diagnostics in these countries. Semi-structured interviews were conducted with n = 18 gynecologists in Germany, Poland and Russia. The interviews were analyzed using the methods of content analysis and thematic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Pregnancy is a stressful period due to various changes and even before the COVID-19 pandemic, studies have shown the need for special care for this category by testing and monitoring during the pregnancy period as well as before becoming pregnant [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy is a stressful period due to various changes and even before the COVID-19 pandemic, studies have shown the need for special care for this category by testing and monitoring during the pregnancy period as well as before becoming pregnant [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…While concerns about routinisation of NIPT appear widely in the literature [ 36 ], the debate is particularly charged in the German context. Research comparing views on NIPT in Germany, Poland and Russia demonstrated a particular focus placed on routinisation in Germany [ 37 ]. Similar results were generated by a comparison of the debate in Germany and Israel [ 38 ].…”
Section: Framing Nipt: ‘Lifestyle’ or ‘Medical’ Technologymentioning
confidence: 99%